Waste into Rupiah: Empowering Pre-prosperous Households ThroughWaste Management Program in Bandar Lampung City - Irwandani Irwandani; Akbar Handoko; Muhammad Farhan Barata; Bella Satiyo Putri (Smart Society, 2025)
Waste management in Bandar Lampung has reached a critical point, with significant environmental and public health implications. This community engagement initiative, titled "Turning Waste into Rupiah," focuses on empowering underprivileged households through waste management programs. Drawing on the Asset-Based Community Development (ABCD) framework, the program integrates local resources and emphasizes community participation to address waste-related challenges. The theoretical underpinning aligns with community empowerment and sustainable development principles, aiming to enhance environmental awareness and economic opportunities. The project employed a participatory approach involving 55 pre-identified low-income households in Way Dadi, Sukarame. Activities included training sessions on waste segregation, recycling, and value-adding practices like making plastic-stuffed cushions and compost production. Surveys and workshops were conducted to assess participants' knowledge, behavior, and potential in waste management. Key outcomes showed that while 58.2% of participants recognized the economic potential of waste, only 14.5% consistently practiced segregation. Post-training, participants demonstrated improved skills and produced marketable products, including compost and cushions. Collaborations with local stakeholders, including recycling industries and municipal authorities, ensured sustainable program implementation. The initiative effectively bridged environmental conservation with economic empowerment, showcasing the dual benefits of waste management.This program highlights the transformative power of community engagement in addressing environmental issues while fostering economic resilience. Future efforts should focus on scaling up such initiatives to broader populations and enhancing long-term impact through policy support and continued community involvement.